Penerapan Konsep Kepemimpinan Islam ala Rasulullah SAW. Pada Bisnis Cafe (Studi Kasus Pada Lafayette Coffee & Eatery) - Sahid, Sahid; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to explore the model of leadership of Prophet Muhammad SAW and how the concept of Islamic leadership is applied at Lafayette Coffee & Eatery. The research method used is qualitative, employing primary data. The data was collected through interviews with employees and managers of Lafayette Coffee & Eatery. The findings reveal that the model of Prophet Muhammad SAW’s leadership comprises four characteristics: siddiq (honesty), fathanah (intelligence), tabligh (communication), and amanah (trustworthiness). These four characteristics represent the core values of the Islamic leadership concept. Additionally, the study found that the concept of Islamic leadership is a fundamental value that inspires the management practices at Lafayette Coffee & Eatery. This concept has become a living and evolving tradition, as reflected in the SOPs at Lafayette Coffee & Eatery, such as mandatory prayers, playing the adhan audio at prayer times, delivering a brief religious talk after the adhan, and reciting Quranic verses. Moreover, the four characteristics of Prophet Muhammad SAW’s leadership guide the attitudes and behaviors of both managers and employees at Lafayette Coffee & Eatery. Keywords: Islamic Leadership, Leadership of Prophet Muhammad SAW, F&B Industry, Islamic Leadership Characteristics